Diffusing capacity of gills of a hill-stream fish Glyptothorax telchitta (Hamilton-Buchnan) in relation to body weight - Subba, Bharat Raj; Ghosh, Tapan Kumar; Roy, Prabhat Kumar (Nepalese Journal of Biosciences, 2018)
The diffusing capacity of the gills of Glyptothorax telchitta was determined in relation to body weight by calculating harmonic mean of the thickness of water blood diffusion barrier from different regions of the secondary lamellae. The harmonic mean was 1.7202 μm, whereas the arithmetic mean was found to be 2.607 μm, which was more than the harmonic mean. The thickness of the water blood pathway varied from 0.77 to 7.70 μm. The diffusing capacity Dt (ml O2 min-1 mmHg-1) has been found to increase with increasing body weight by a power of 0.7008. As the slope of the diffusing capacity is less than 1.0, the weight specific diffusing capacity Dt1 (ml O2 min-1 mmHg-1 Kg-1) decreases with increasing body weight by a power of -0.2996.